Eksplorasi Kesulitan Belajar Anak SlowLearning Di Sekolah Dasar : Study Kasus Pada Anak Kelas 4 - Nafsiyani; Nurratri Kurniasari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to explore learning difficulties experienced by slow learner students in grade IV of Elementary School through an in-depth case study. The subjects of the study consisted of three students, class teachers, and parents as additional informants. Data collection techniques were carried out through observation, in-depth interviews, and documentation of student learning outcomes, which were then analyzed using a thematic approach. The results of the study showed that slow learner students had difficulty understanding complex verbal instructions, took longer to complete tasks, and showed obstacles in basic skills such as reading, writing, and arithmetic. From the socio-emotional aspect, students also showed low levels of academic self-confidence and a tendency to withdraw from social interactions in the classroom. These findings underline the importance of implementing adaptive and differentiated learning strategies, including the use of visual and concrete media, gradual learning approaches, and consistent emotional and social reinforcement. This study provides implications for the implementation of inclusive education in elementary schools, emphasizing the importance of collaboration between teachers, schools, and parents in building a learning environment that is responsive to the needs of slow learner students.